The Examination of Sports Club Managers’ Attitudes toward Healthy Nutrition - Atali, Levent; Tarim, Tahir; Altuntaş , Talha; Atali, Makbule (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the attitudes of amateur sports club managers toward healthy nutrition in different variables. Method: The study’s data was obtained using the Attitude toward Healthy Nutrition Scale, which has 21 elements and four sub-dimensions. The t-test was used to examine the difference between the obtained ATHNS dimensions according to gender and nutritional education. The analysis of variance (ANOVA) test was used to examine the study’s dimensions according to education, age, and monthly income level, and the Sidak test for paired comparisons. Results: The attitude toward healthy nutrition (ATHN), feeling toward nutrition (FTN), positive nutrition (PN), and malnutrition (MN) levels of the female and male participants were similar (p> 0.05). In the study, it was found that (ATHN) levels of some age groups were lower than the participants in other age groups (p <0.05). It was observed that the NK levels of the participants whose income levels were 6001-7000 TL were higher than the other income groups determined in the study group (p <0.05). It is seen that the participants’ education level differ according to their (NK) level. In the study, it was observed that the NK levels of the high school and associate degree participants (NK) were higher than the undergraduate and graduate graduates (p <0.05). Conclusion: As a result, sports club managers need to have known both their health and managing processes related to nutrition in the sports club they manage. Also, it should be ensured that managers receive training on nutrition, and their level of knowledge on this subject should be at a sufficient level regarding nutritional conditions that may affect the athletes’ performance. In this study, it was concluded that variables such as age, education, and income levels affect sports club managers to have nutritional knowledge.